A Potential Candidate for Lamp Phosphor: Eu3+ Activated K2Y2B2O7. (10th April 2014) - Koparkar, K. A.; Bajaj, N. S.; Omanwar, S. K.
Abstract : The novel phosphor K2 Y2 B2 O7 doped with europium is studied for its photoluminescence properties. The studies show that the phosphor gives strong red emission (PL) at 613 nm related to 5 D0 - 7 F2 transition of Eu 3+ under the 260 nm excitation (PLE) related to the charge transfer (CT) from the 2p orbital of the O 2− ions to the 4f orbital of Eu 3+ ions with CIE coordinates (x = 0.675 ;y = 0.324 ). The results of PL and PLE spectra indicate the applicability of K2 Y2 B2 O7 :Eu as a red component in lamp phosphor. The phosphor is characterized through XRD pattern analysis, and morphology is explained on the basis of SEM image. Optimum concentration of Eu 3+ required for the highest intensity of emission is also studied.